Sistem Informasi Akuntansi Berbasis Microsoft Access Utama Motor - Hendi, Hendi; Novi, Novi (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to develop a Microsoft Access-based accounting information system for Utama Motor, a small and medium enterprise (SME) in Batam, Indonesia, to improve the efficiency and accuracy of financial recording. Previously, financial transactions were recorded manually using Microsoft Excel, often resulting in input errors, data duplication, and delays in preparing financial statements. The system was designed using a relational database structure, comprising main tables such as msChartofAccount, msInventory, msSupplier, and trSalesHeader to integrate financial transactions. The research employed a Participatory Action Research (PAR) approach, emphasizing active collaboration between researchers and the business owner throughout the design, testing, and evaluation stages. The implementation results show a 42% reduction in financial report preparation time, improved recording accuracy, and higher user acceptance levels. Furthermore, the system produces financial statements that comply with the Indonesian Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Overall, the Microsoft Access-based system offers an effective and affordable solution for SMEs to enhance financial management professionalism and support digital transformation in small enterprises.